The Evolution of Wisteria Vein Mosaic Virus: A Case Study Approach to Track the Emergence of New Potyvirus Threats - Massimiliano Morelli; Giusy D’Attoma; Pasquale Saldarelli; Angelantonio Minafra (Pathogens)
Wisteria vein mosaic virus (WVMV, Potyvirus wisteriae), a virus belonging to the genus Potyvirus, is responsible for Wisteria vein mosaic disease (WMD), a severe disease that affects Wisteria, a genus of garden plants acclaimed worldwide. Although probably originating in the Far East, WVMV infection was first reported in the US, and subsequently in numerous countries. Following the first molecular detection of an Italian isolate, WVMV Bari, its full-length genome was achieved using NGS barcoding technology. A PhyML phylogenetic analysis, supported by clustering algorithm validation, identified a clear separation between two phylogroups. One major clade comprised WVMV strains isolated from Wisteria spp. A second clade grouped three highly divergent strains, at the borderline species threshold, all found in non-wisteria hosts. Relying on a Relative Time Dated Tips (RTDT) molecular clock, the first emergence of WVMV clades has been traced back to around the 17th century. A network inference analysis confirmed the sharp separation between the two host-related phylogroups, also highlighting the presence of potential intermediate variants. Inter-population genetic parameters revealed a very high genetic differentiation in both populations, which was made reliable by statistically significant permutation tests. The migrant number (Nm) and fixation index (FST) evidenced a restricted gene flow and strong population structures. According to the dN/dS ratio and negative neutrality tests, it was derived that purifying selection at the expense of non-silent variants is underway within WVMV populations. Targeting WVMV evolutionary traits, the present effort raised interesting questions about the underestimated potential of this culpably neglected species to spread in economically relevant crops. The main intention of our study is, therefore, to propose an evolution-based analysis approach that serves as a case study to investigate how other potyviruses or newly emerging viruses may spread.